The Role of Islamic Religious Education in Promoting Dialogue and Interreligious Tolerance in Indonesia - Hani Zahrani; Desi Asmarita; Siti Zakiah Ramadhani (Sekolah Tinggi Agama Islam Solok Nan Indah, 2026)
This study examines the role of Islamic Religious Education in promoting dialogue, tolerance, and interreligious harmony within Indonesia’s multicultural society. This study employs a qualitative method with a content analysis approach toward literature related to religious pluralism, interreligious relations, and Islamic moderation. The research data were obtained from books, scholarly journal articles, and previous studies relevant to the topic of discussion. The findings reveal that Islamic Religious Education plays a significant role in shaping students’ understanding of Islam as a religion that upholds the values of peace, justice, compassion, and respect for diversity. Through the integration of universal Islamic values into the learning process, Islamic Religious Education has the potential to encourage open, respectful, and empathetic communication across religious boundaries. However, the implementation of tolerance-oriented Islamic Religious Education still faces several challenges, including the dominance of normative teaching approaches, limited teacher competence in multicultural education, and the insufficient integration of interfaith dialogue principles into formal curricula. Therefore, strengthening educational policies, enhancing teacher capacity, and developing innovative pedagogical models based on the spirit of religious moderation (wasathiyah) are essential steps in cultivating tolerant, inclusive, and peace-oriented individuals within Indonesia’s pluralistic society.